Meningkatkan Pembelajaran Senam Sumedang Simpati dengan Menggunakan Media Audio Visual di SDN Bongkok - Yuliantika, Mega; Suherman, Ayi; Safari, Indra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research uses audio-visual learning media to improve student learning outcomes in Sumedangsympathetic gymnastics learning at SDN Bongkok. This research uses a mixed-method research method with a classroom action research design and a Kemmish and Mc—Taggart model research design whose cycle or cycle has stages: planning, action, observation, and reflection. The instruments used in this research were tests, observation, and documentation. The participants were elementary school students in grade IV (four) at SDN Bongkok, Paseh subdistrict, Sumedang district, with 26 students. In this study, the results showed that in cycle I, nine people were declared complete with a completion percentage of 34.6%, while the students who had not yet completed were 17 students with a percentage of 65.4%. In the second cycle, 15 students completed with a percentage of 57.7%, while 11 students did not complete with a percentage of 42.3%. A significant increase occurred in cycle III, where 24 students completed with a percentage of 92.3% and two students who did not complete with a percentage of 7.7%. The conclusion is that using audio-visual learning media in Sumedang Simpati gymnastics can improve student learning outcomes at SDN Bongkok. Keywords: audiovisual media, Gymnastics learning, Sumedang Simpati